Multilateral investment disciplines: Don't forget the GATS! - Rudolf Adlung (Columbia University, Vale Columbia Center on Sustainable International Investment (VCC), 2014)
In discussions about the need for, and possible role of, a multilateral framework for investment, existing obligations under the General Agreement on Trade in Services (GATS) are seldom acknowledged. However, some two-thirds of the world's FDI stock are in services and, thus, potentially subject to the GATS which, in addition to MFN clauses in BITs, operates as an external "multilateralizer" of trade and investment conditions in services.
Keywords: 330